PELATIHAN PEMBUATAN CAIRAN PENGKILAP MOTOR DI DESA NAGASARI - Pratama, Krisna Yudha; Muis, Abdul; Rofieq, Ainur (Universitas Islam 45 Bekasi, 2024)
In an increasingly advanced development in this modern era, many people use vehicles, one example is motorbike vehicles, the increasing number of motorbikes makes some or a handful of people who do not take care of the motorbike body, because of this the motorbike body looks dull, so a Real Work Lecture (KKN) will be held in Nagasari Village, Serang Baru District, Bekasi Regency. This community service programme is carried out with the aim of training the community to make them aware of the importance of taking care of the washed motorbike body so that by washing the motorbike it looks clean and tidy. In its implementation, KKN participants used a training method that was carried out to the community in the form of making shiny liquid for motorbike bodies. Community service or youth has a positive impact, namely increasing knowledge and understanding of the importance of caring for the body of a motorbike and making motorbike body polish liquid so that the community or youth can be developed as a form of business, able to care for their own vehicle body.